Transcriptomic analysis of the honey bee (Apis mellifera) queen brain reveals that gene expression is affected by pesticide exposure during development. - Myra Dickey; Elizabeth M Walsh; Tonya F Shepherd; Raul F Medina; Aaron Tarone; Juliana Rangel (PLoS ONE, 2023)
Honey bees (Apis mellifera) play a pivotal role in agricultural production worldwide, primarily through the provision of pollination services. But despite their importance, honey bee health continues to be threatened by many factors, including parasitization by the mite Varroa destructor, poor queen quality, and pesticide exposure. Accumulation of pesticides in the hive's comb matrix over time inevitably leads to the exposure of developing brood, including queens, to wax contaminated with multiple compounds. Here, we characterized the brain transcriptome of queens that were reared in wax contaminated with pesticides commonly found in commercial beekeeping operations including either (a) a combination of 204,000 ppb of tau-fluvalinate and 91,900 ppb of coumaphos ("FC" group), (b) a combination of 9,800 ppb of chlorpyrifos and 53,700 ppb of chlorothalonil ("CC" group), or (c) 43,000 ppb of amitraz ("A" group). Control queens were reared in pesticide-free wax. Adult queens were allowed to mate naturally before being dissected. RNA isolated from brain tissue from three individuals per treatment group was sequenced using three technical replicates per queen. Using a cutoff log2 fold-change value of 1.5, we identified 247 differentially expressed genes (DEGs) in the FC group, 244 in the CC treatment group, and 668 in the A group, when comparing each group to the control. This is the first study to examine the sublethal effects of pesticides commonly found in wax (particularly amitraz) on the queen's brain transcriptome. Future studies should further explore the relationship between our molecular findings and the queen's behavior and physiology.